Convective Baking Characteristics and Effective Moisture Diffusivities of Yellow Mealworms - Seah, Wei Hon; Wong, Alecia Sze Mun; Naik, Wei Qin Nie; Tan, Chun Mun; Chiang, Choon Lai; Hii, Ching Lik (ASEAN Journal of Chemical Engineering, 2020)
ellow mealworm is an alternative protein source studied by researchers to provide an alternative supply of protein to meet the growing demands of human consumption. In this research, convective baking of yellow mealworms at 80°C, 100°C, and 120°C was carried out to study the baking kinetics and product quality. Studies showed the typical falling trend of the moisture ratio curves, which are typical for most bioproducts that undergo hot air treatment. Mathematical modelling showed that the Page model gave a good prediction on the baking kinetics with high fitting accuracy (R2>0.99). Effective diffusivities were determined from 1.66 x 10-11 to 2.88 x 10-11 m2/s within the temperatures tested. The activation energy was estimated at 15.7 kJ/mol based on the Arrhenius equation. The final baked samples appeared darker in color because the browning reaction and reduction in bulk density and product length were observed in the range of 48-54% and 3.0-16.3%, respectively.